KORELASI LAJU FILTRASI GLOMERULUS, HEMOGLOBIN, SATURASI OKSIGEN DAN KOMORBID DENGAN KADAR LAKTAT PASIEN PENYAKIT GINJAL KRONIS STADIUM TERMINAL - Tantri, Ni Luh; Lahmadi, Iqbal; W Soeatmadji, Djoko; -, Nursamsu (journal of internal medicine, 2011)
Hyperlactatemia usually happen in Chronic Kidney Disease (CKD) patients and it can used as indicator how bad theoxygen perfusion to organs. Therapy for hyperlactatemia is Hemodialysis (HD). Some studies assume few factors thatcorrelate to the level of lactate post HD, such as improving of Glomerulus Filtration Rate (GFR), level of hemoglobin(Hb), oxygen saturation and accompany diseases. An analytic cross sectional study was carried out in Saiful AnwarHospital to deÞ ne correlation between GFR, level of Hb, oxygen saturation and accompany diseases with level of lactatepost HD. Forty three samples were included. There were signiÞ cant correlation between level of lactate post HD withlevel of Hb (p = 0.000) and GFR (p = 0.006). With multivariate models, there were signiÞ cant correlation between levelof lactate post HD with those factors (p = 0.000). Using linier regression entering those variables into model, it foundformula level of lactate = 3.719 ! 0.196 (Hb) ! 0.053 (GFR). There was signiÞ cant correlation between between level oflactate post HD with GFR, Hb, oxygen saturation and accompany diseases.